Microcontroller-Based Air Pollution Monitoring System - Chumaidi, Ahmad Fatich; Sujono, Sujono; Hariono, Tholib (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The increase in air pollution is a serious environmental issue in many major cities in Indonesia. This study aims to develop an effective and efficient air pollution monitoring system using a microcontroller. The designed system consists of air pollution sensors capable of detecting various pollutants such as PM10, CO2, and NO2. The data collected from the sensors are processed by the microcontroller and displayed in real-time to users through a web-based interface. This method allows users to accurately and promptly monitor the air quality in their surroundings. The results show that the microcontroller-based monitoring system operates stably and provides accurate data on the concentration of pollutants in the air. This system is expected to be a valuable tool for the general public and authorities in monitoring and managing air quality, as well as taking preventive measures against the adverse effects of air pollution.